Addressing Structural Discrimination: Recommendations for an Inclusive Curriculum Policy for Non-Muslim Students in Papua at State Islamic Religious Universities - Taufik Hidayah Santoso (AMUYA: JOURNAL OF MANAGEMENT, 2026)
This policy paper provides an overview of the non-Muslim student admission policy at State Islamic Religious Higher Education Institutions (PTKIN) in Papua Province facing significant implementation challenges, which have the potential to perpetuate structural discrimination and hinder the achievement of academic equity. This gap is rooted in three fundamental policy issues: Lack of Adaptation of the Compulsory Religious Curriculum, minimal Pedagogical Competence of Lecturers in a Multicultural context, and the priority of lecturer training that is still functional, failing to internalize the principles of true Inclusive Education. The analysis of this policy problem is carried out by identifying the main problems and specific causes, followed by a priority assessment using the USG (Urgency, Seriousness, Growth) method, which confirms that curriculum issues are the most pressing issues. To formulate solutions, William N. Dunn's alternative policy scoring analysis is used with the criteria of Effectiveness, Efficiency, Adequacy, and Equity, and supported by the foundation of Culturally Responsive Pedagogy Theory and the regulatory mandate of the National Education System Law. The results of this analysis recommend the issuance of a single regulation as the most optimal intervention, namely the Rector's Regulation on Guidelines for Accommodation of Compulsory Interfaith Curriculum. This recommendation should be accompanied by the establishment of an Inclusive Development Center (PPI) to ensure institutional accountability and appropriate investment in lecturer capacity development, ensuring PTKIN's transition from symbolic acceptance to systemic integration that is equitable and relevant to Papua's multicultural context.